The Impact of Afghan Refugees on the local people of Balochistan - Yaseen, Dr. Muhammad; Jan, Dr. Amir; Baloch, Gohram; Rab, Dr. Abdul; Munir, Gulshan (The journal of contemporary issues in business and government, 2021)
The present research examines the impacts of Afghan refugees on the local people of Balochistan. The prolonged refugees had generated sever changes in the social, economic, environmental, political and cultural aspects on the host society. The factors included in the study were; health, education, economic, shelter, social disorder, insecurity, unemployment, spread of arms, cheap labour force. Universe of the study was Balochistan. The nature of study was qualitative and purposive sampling was used to collect the data. Tool of the data was an interview schedule. The interviews were conducted with the local administrative personnel’s and key informants of the selected areas. It is found that protracted refugees had left out drastic impacts on the local population both socially and economically. Their health, education, economic activities, water and sheltering were badly affected by the refugees. The local people felt insecure in their own residential areas due to the presence of refugees.